THE EFFECT OF HALAL LABELIZATION, PRODUCT QUALITY AND BRAND IMAGE ON THE PURCHASE OF MS GLOW IN KEDUNGWARINGIN DISTRICT BEKASI - Basar Maringan Hutauruk; Arief Teguh Nugroho (SEAN Institute, 2022)
Purchasing decisions are where individuals evaluate various options and decide on a choice of a product. Purchase decisions can be influenced by several factors such as halal labeling, product quality, and brand image. The purpose of this study was to determine the effect of halal labeling, product quality, and brand image on purchasing decisions for MS Glow products. This type of research uses quantitative methods. The population of this study were consumers of MS Glow products in Kedungwaringin District with a total sample of 100 respondents. This study used primary data obtained from the distribution of questionnaires. The sampling technique in this study used a perposive sampling technique with the slovin formula. for data collection includes observation, distributing questionnaires, and literature study. Data analysis in this study used validation test, reliability test, classic assumption test, multiple linear regression test, and hypothesis testing. The research which was processed using the SPSS version 23.0 for windows program in the T test showed that Halal Labeling had a significant effect on Purchase Decisions because it obtained the results of Tcount > T table or 4.909 > 1.984 and sig value 0.00 < 0.05. Product quality has a significant influence on Purchase Decisions, the results of T count > T table or 5,648 > 1,984 and sig value 0.00 < 0.05 and Brand Image has a significant influence because it obtains Tcount > T table or 7,057 > 1,984 and sig 0 ,00 < 0.05. And the results of the F test stated that Fcount 71.649 > 2.697 Ftable and significance 0.000 <0.05, meaning that Halal Labeling, Product Quality, and Brand Image have a simultaneous effect on purchasing decisions.